2022
DOI: 10.1039/d1se02040d
|View full text |Cite
|
Sign up to set email alerts
|

Efficient electrocatalytic H2 evolution mediated by 2D Janus MoSSe transition metal dichalcogenide

Abstract: Recently, 2D Janus Transition Metal Dichalcogenides (JTMDs) with asymmetric electronic structures are inviting an intense research interest in modern science and technology. Using the first principles-based periodic hybrid dispersion-corrected Density...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 74 publications
(208 reference statements)
1
23
0
Order By: Relevance
“…50,51 This is a well-established molecular cluster model system to investigate electrocatalytic activities, such as the HER, and there are several studies about the cluster model systems like MoS 2 , MoSSe and Mn-doped MoS 2 , which can be found in ref. 9, 50 and 51. The results showed that the Se-edges of the 2D MoSe 2 have similar hydrogen binding as the Mo-edge of MoSe 2 , i.e.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
See 3 more Smart Citations
“…50,51 This is a well-established molecular cluster model system to investigate electrocatalytic activities, such as the HER, and there are several studies about the cluster model systems like MoS 2 , MoSSe and Mn-doped MoS 2 , which can be found in ref. 9, 50 and 51. The results showed that the Se-edges of the 2D MoSe 2 have similar hydrogen binding as the Mo-edge of MoSe 2 , i.e.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
“…60 This mixed kind of basis set has been extensively used to study the transition metal containing systems in density functional theory methods to explore the chemical reactions, and provides reliable results. 50,51,59…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…; however, both the approaches provide comparable findings and outcomes, i.e., both the VASP and CRYSTAL17 codes provide similar results. 45,48,56,57 VESTA, 58 a visualization code, was used to create graphics and analyze the crystal structure of all the systems.…”
Section: Paper Pccpmentioning
confidence: 99%